Preliminary Design Analysis And Fabrication Of MYSAT Structure - Amir, Mohammed Hazrieq Hasief (Universiti Sains Malaysia, 2017)
MYSat is the first satellite ever in which is built by the university student from (Universiti Sains Malaysia) USM. The structural subsystem of MYSat is specifically designed to support the mission of MYSat. The external dimension of the CubeSat must be compatible with the deployer interface, which in this case is the Japanese Experiment Module Small Satellite Orbit Deployer (J-SSOD). Besides, the CubeSat structure must also undergo several structural analysis as required by a J-SSOD service provider, Japan Aerospace eXploration Agency (JAXA). This thesis focuses on the chassis design of MYSat to refine structure subsystem’s requirements according to the mission objectives. The structure has been designed and fabricated by 3D printer and then CNC Machine to examine the design flaws and fitting and suitability of manufacturing process. The structural analysis has also been performed on the model using ANSYS to demonstrate the ability of MYSat structure to withstand the loads. Two type of chassis have been studied which is modular frame and monoblock. The result shows that monoblock have higher frequency in modal analysis 219.52Hz compare to modular frame which is 247.32. Monoblock approach offers the best relationship between rigidity and mass but has the disadvantage of significantly increase the complexity of assembly procedures. Lastly, at the end of this work, there will be a few future recommendation for future research in regards to this project.